2011
DOI: 10.53841/bpsicpr.2011.6.1.71
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study evaluating strengths-based coaching for primary school students: Enhancing engagement and hope

Abstract: Objective:This pilot study examines the impact of an evidence-based strengths coaching programme on male primary school students’ levels of engagement and hope.Design:In a within-subject design study, 38 Year Five male students (mean age 10.7 years) participated in a strengths-based coaching programme as part of their Personal Development/Health programme at an independent, private primary school in Sydney, Australia.Method:Participants were randomly allocated to groups of four or five with each group receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(24 citation statements)
references
References 25 publications
1
22
0
1
Order By: Relevance
“…Self-reported strengths knowledge and use have been identified as major predictors of subjective wellbeing in both cross-sectional and longitudinal studies among different age groups (e.g., Govindji & Linley, 2007;Proctor et al, 2011;Quinlan, Swain, Cameron, & Vella-Brodrick, 2015;Sheldon, Jose, Kashdan, & Jarden, 2015;Waters, 2015a;Wood, Linley, Maltby, Kashdan, & Hurling, 2011). Strength use was associated with hope and positive coping in child samples (Madden, Green, & Grant, 2011;Waters, 2015b), life satisfaction and self-esteem in adolescents (Proctor et al, 2011;Suldo, Savage, & Mercer, 2014;Waters, 2015a), subjective wellbeing, selfesteem, self-efficacy, and life satisfaction in college samples (Allan & Duffy, 2014;Douglass & Duffy, 2015;Proctor et al, 2011), and happiness in adult samples (Seligman, Steen, Park, & Peterson, 2005). While some studies have shown that both self-reported strength knowledge and use are associated with subjective wellbeing (Govindji & Linley, 2007), in some studies, self-reported strength use was found to be the strongest predictor of wellbeing (Linley, Nielsen, Gillett, & Biswas-Diener, 2010).…”
mentioning
confidence: 99%
“…Self-reported strengths knowledge and use have been identified as major predictors of subjective wellbeing in both cross-sectional and longitudinal studies among different age groups (e.g., Govindji & Linley, 2007;Proctor et al, 2011;Quinlan, Swain, Cameron, & Vella-Brodrick, 2015;Sheldon, Jose, Kashdan, & Jarden, 2015;Waters, 2015a;Wood, Linley, Maltby, Kashdan, & Hurling, 2011). Strength use was associated with hope and positive coping in child samples (Madden, Green, & Grant, 2011;Waters, 2015b), life satisfaction and self-esteem in adolescents (Proctor et al, 2011;Suldo, Savage, & Mercer, 2014;Waters, 2015a), subjective wellbeing, selfesteem, self-efficacy, and life satisfaction in college samples (Allan & Duffy, 2014;Douglass & Duffy, 2015;Proctor et al, 2011), and happiness in adult samples (Seligman, Steen, Park, & Peterson, 2005). While some studies have shown that both self-reported strength knowledge and use are associated with subjective wellbeing (Govindji & Linley, 2007), in some studies, self-reported strength use was found to be the strongest predictor of wellbeing (Linley, Nielsen, Gillett, & Biswas-Diener, 2010).…”
mentioning
confidence: 99%
“…However, self-esteem and perceived stress were not influenced by the intervention. The approach to mental health in schools tends to be reactive rather than proactive with resources only being made available to students when students demonstrate difficulties (Madden, Green & Grant, 2011). Peer coaching may be a beneficial, low cost, proactive method to support students during stressful periods.…”
Section: Discussionmentioning
confidence: 99%
“…Coaching psychology has been described as a collaborative and solution focused practice. It is designed to enhance wellbeing, facilitate goal attainment and create purposeful, positive change (Law, 2013;Madden, Green & Grant, 2011).…”
Section: Coachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirically researched and evaluated programs, which could be delivered by SCs, have also been found to reduce psychological disorders in the short and long term (Gillham et al, 2007;Gillham et al, 1995;McGrath & Noble, 2003). Research around the effectiveness of evidence-based coaching to enhance student wellbeing, as well as support academic achievement and engagement, continues to grow (e.g., see Dulagil et al, 2016;Green et al, 2008;Madden et al, 2011).…”
Section: Counsellor As Coachmentioning
confidence: 99%